Die Basilika in Byzanz Gestalt, Ausstattung und Funktion sowie das Verhältnis zur Kreuzkuppelkirche - Altripp, Michael (Millennium-Studien / Millennium Studies, 2013)
In Byzantium, the central structure is considered archetypical. This study shows that this assumption is only partly true. It presents the basilicas of the 7th to 15th centuries, addressing questions of typology, appointments, function, and the relationship to longitudinal and central constructions. It shows that the Byzantines were more flexible in their approach to these construction types than previously assumed, a conclusion supported by theological evidence.